(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The digitalization of the battlefield creates conditions for an unprecedented enlargement in mobility and parallelism of combat operations. The resulting effect is the increased complexity in implementing the command and coordination functions of the command and control (C2) systems. C2 networks, as the communication infrastructure of C2 systems for issuing orders and disseminating information in real time, are a key element for data exchange between commanders, troops and other related organizations. The characteristics and evolutionary behaviour of C2 networks are described by complex hierarchical associations, interwoven communication links, and dynamic changes. It is their complexity that has become the subject of innovative research approaches and created some of the latest scientific products in the field of C2 systems. The research focus in this report is directed at presenting and comparing typological varieties of modern networked C2 approaches – hypernetworks and supernetworks. Hypernetworks are neural networks that generate weights for another neural target network, and are useful in describing C2 networks with complex levels, intertwining connections and dynamic topology. Supernetworks are a networking technique that consolidates multiple smaller networks into a larger one, simplifying routes and reducing their size. The comparison of the particular variations of the theories is carried out in order to identify the areas of application and solved tasks. References to the C2 networks of the C2 systems in the Bulgarian Armed Forces are provided.